Pengaruh Segmenting, Targeting dan Positioning terhadap Keputusan Pembelian : (Studi pada Konsumen Aplikasi Online Shop Tokopedia di Jakarta) - Fauzi Alfi Yassin; Rina Ayu Vildayanti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
The purpose of this study is to know the effects of Segmenting, Targeting and Positioning of purchase decisions (study on the consumer of the online store store application in Jakarta). Samples used by as many as 95 respondents who have previously shoated on the online application for shop pedia by using a quantitative research method between the research variables through testing hypotersis. The variables in this study consist of purchasing decisions, and the independent variables of segmentation, isolation, and positioning. Testing of data and results in sports using a stastical package of social science (SPSS) analysis package. Studies have shown that no decisions can be made on purchase, absences can affect purchase decisions, and positioning effects will result in purchasing decisions. Segmenting, Targeting and Positioning simultaneously account for purchasing decisions.